Pengaruh Media Pembelajaran Kahoot terhadap Kemampuan Berpikir Kritis Siswa pada Jurusan Teknik Komputer dan Jaringan di SMK Muhammadiyah 1 Malang - Dian Indrawati; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The purpose of this study was to find out how the results of the influence of kahoot learning media on students' critical thinking skills in the TKJ major at SMK Muhammadiyah 1 Malang. This research method uses quantitative research methods that involve numbers to be processed and statistical calculations. This study used a sample of 47 students, data collection in this study used a questionnaire with a Likert scale. The hypothesis testing technique uses the calculation of correlation analysis, partial testing of the T test, testing the coefficient of determination and simple linear regression analysis. The results of this study indicate that the kahoot learning media used in the evaluation of learning partially does not affect the critical thinking skills of students in grade 10 majoring in TKJ, as evidenced by the results of the t-test calculation that the t-count value is 1.717 and the sig value is 0.93. So the decision is 1.717 < 2.014 and 0.093 < 0.05, it can be concluded that H0 is accepted and the R2 coefficient value is 0.062 which means that the influence of kahoot learning media on critical thinking is 6.2% while 93.8% other variables affect it.